2000
DOI: 10.1021/jf000563u
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Chemical Changes in Olive Juice and Brine during Green Olive Fermentation

Abstract: Changes in physicochemical characteristics, substrate depletion, and product formation during fermentation were followed in both brine and olive juice in order to achieve a complete knowledge of fermentation chemistry in Spanish-type green olives. Both spontaneous and controlled fermentations were investigated. Fermentation rate, irrespective of the type of fermentation, was lower in olive juice than in brine, but the main acid products eventually reached equilibrium. Final free acidity remained significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 8 publications
4
41
0
Order By: Relevance
“…In this way, Sánchez et al (2000) and Montaño et al (2003) reported the formation of acetic acid, succinic acid, formic acid, ethanol, and acet aldehyde, all of them usually produced by yeasts, during green olive fermentations. The esterase and lipase activities exhibited by diverse yeast species could also improve the aromatic profile of fermented olives by increasing their free fatty acid content (Hernández et al, 2007; Rodríguez-Gómez et al, 2010,2012).…”
Section: Use Of Yeast Starters With Technological Applications In Tabmentioning
confidence: 97%
“…In this way, Sánchez et al (2000) and Montaño et al (2003) reported the formation of acetic acid, succinic acid, formic acid, ethanol, and acet aldehyde, all of them usually produced by yeasts, during green olive fermentations. The esterase and lipase activities exhibited by diverse yeast species could also improve the aromatic profile of fermented olives by increasing their free fatty acid content (Hernández et al, 2007; Rodríguez-Gómez et al, 2010,2012).…”
Section: Use Of Yeast Starters With Technological Applications In Tabmentioning
confidence: 97%
“…Equilibration of fermentable substrates and NaCl may affect the fermentation rate (Sànchez et al, 2000). Besides the use of starter cultures and different salt levels, the application of a highly acidified solution, with acetic or lactic acid, is an alternative to preserve the product.…”
Section: Total Polyphenols Of Olivesmentioning
confidence: 99%
“…In the last decades many efforts have been made to study the aromatic fraction of fermented olives based mainly on chromatographic determinations [2][3][4][5][6][7][8][9]. However, these analytical techniques are also time-consuming and require sophisticated equipment and skilled personnel.…”
Section: Introductionmentioning
confidence: 99%